Optimizing the Demineralizer Water Control System Centrally in Waste Heat Recovery Power Generation by Applying the PDCA Cycle - Refki Budiman; Queen Hesti Ramadhamy; Muhammad Arya Diwa; Imil Hamda Imran (LPPM Universitas Andalas, 2026)
The cement production process consumes a significant amount of energy, particularly during the clinker burning stage. This stage generates high-temperature exhaust gases. Waste Heat Recovery Power Generation (WHRPG) technology captures this waste heat from the kiln to generate electricity; however, its efficiency largely depends on the quality of demineralized water. This study focuses on improving demineralized water quality through the implementation of a centralized control system based on the Plan, Do, Check, Action (PDCA) method. In the Plan phase, the root causes identified were delays in performing water regeneration and manual control of the demineralization process. As an alternative solution to these dominant causes, a centralized control system was proposed for the demineralizer area, located in the control room. The results show that the centralized system effectively reduced water conductivity to below 2 µS/cm, in accordance with the required standards. This improvement led to financial benefits of IDR 300,672,000 per year through reduced water replacement and boiler damage. Additionally, it provided non-financial benefits such as simplified operations and reduced maintenance needs. The established standards for input, process, and output contribute to the continuous improvement of WHRPG operational efficiency, thereby supporting more effective energy management in the cement industry.